Pirates of the Caribbean : The curse of the black pearl - Elliott, Ted (Penguin Readers, 2008)
The Black Pearl, a cursed pirate ship that haunts the seas with tattered black sails and a vicious crew, has just materialized in Port Royal and stolen away the governor's daughter, Elizabeth Swann. Will Turner, a young blacksmith in love with Elizabeth, sets sail to rescue her by whatever means necessary--even enlisting the help of a pirate! Enter Captain Jack Sparrow, a cunning and charismatic pirate with his own personal stake in the mission...the Black Pearl was once his ship and he aims to get it back.